Development of a Super Slim Façade System for InHolland Polytechnic, Delft - M. Eekhout (Challenging Glass Conference, 2010)
The initial conceptual ‘wild idea’ for the INHolland project by architect Rijk Rietveld, New York, was elaborated through different design brainstorms towards a radical innovative system for ultra-slim glass façades. In this façade system insulated glass panels of a depth of maximum 50 mm are integrated with internal pre-stressed structural composite cables, stabilising the façade against wind forces. Dead weight to be taken over by vertical deadweight rods in between the vertical silicone seams between the panels. The insulated glass panels are sealed by composite spacer frames. Many different solitary tests were done with the sealing and the carbon fibre components, with adhesion of silicone sealant on the carbon fibre frames and on the perforation of the carbon fibre used through the frames. In the actual engineering phase structural analysis was performed and tests on several levels were executed. The composite frames were substituted by conventional metal frames. Due to the refusal by the glass panel manufacturer to supply a guarantee on inadequate number of tests with inadequate quality, the integrated system had to be changed into a duosystem with internal pre-stressed cables and integrated dead weight suspension rods. The façade had to keep in pace with the progress on site.